Major Advances in Emerging Degrader Technologies - Luo, Hang; Wu, Li; He, Yujian; Qin, Chong; Tang, Xinjing (Frontiers in Cell and Developmental Biology, 2022)
Recently, degrader technologies have attracted increasing interest in the academic field and the pharmaceuticals industry. As one of the degrader technologies, proteolysis-targeting chimeras (PROTACs) have emerged as an attractive pharmaceutical development approach due to their catalytic ability to degrade numerous undruggable disease-causing proteins. Despite the remarkable progress, many aspects of traditional PROTACs still remain elusive. Its expansion could lead to PROTACs with new paradigm. Currently, many reviews focused on the design and optimization strategies through summarizing classical PROTACs, application in diseases and prospect of PROTACs. In this review, we categorize various emerging PROTACs ranging from simply modified classical PROTACs to atypical PROTACs such as nucleic acid-based PROTACs, and we put more emphasis on molecular design of PROTACs with different strategies. Furthermore, we summarize alternatives of PROTACs as lysosome-targeting chimeras (LYTACs) and macroautophagy degradation targeting chimeras (MADTACs) based on different degradation mechanism despite of lysosomal pathway. Beyond these protein degraders, targeting RNA degradation with the potential for cancer and virus therapeutics has been discussed. In doing so, we provide our perspective on the potential development or concerns of each degrader technology. Overall, we hope this review will offer a better mechanistic understanding of emerging degraders and prove as useful guide for the development of the coming degrader technologies.